Promiscuous Defluorinating Enoyl-CoA Hydratases/Hydrolases Allow for Complete Anaerobic Degradation of 2-Fluorobenzoate - Tiedt, Oliver; Mergelsberg, Mario; Eisenreich, Wolfgang; Boll, Matthias (Frontiers in Microbiology, 2017)
Biodegradation of the environmentally hazardous fluoroaromatics has mainly been associated with oxygenase-dependent defluorination reactions. Only very recently a novel mode of oxygen-independent defluorination was identified for the complete degradation of para-substituted fluoroaromatics in the denitrifying Thauera aromatica: a promiscuous class I benzoyl-coenzyme A (BzCoA) reductase (BCR) catalyzed the ATP-dependent defluorination of 4-F-BzCoA to BzCoA. Here, we studied the unknown enzymatic defluorination during the complete degradation of 2-F-benzoate to CO2 and HF. We demonstrate that after activation of 2-F-benzoate by a promiscuous AMP-forming benzoate-CoA ligase, the 2-F-BzCoA formed is subsequently dearomatized by BCR to a mixture of 2-F- and 6-F-cyclohexa-1,5-diene-1-carboxyl-CoA (2-F-/6-F-1,5-dienoyl-CoA). This finding indicates that BCR is not involved in C–F-bond cleavage during growth with 2-F-benzoate. Instead, we identified defluorination of the two isomers by two enoyl-CoA hydratases involved in down-stream reactions of the BzCoA degradation pathway. (i) The 1,5-dienoyl-CoA hydratase hydrated the F-1,5-dienoyl-CoA isomers to a mixture of the stable 2-F-6-OH-1-enoyl-CoA and the unstable α-fluorohydrin 6-F-6-OH-1-enoyl-CoA; the latter spontaneously decomposed to HF and 6-oxo-cyclohex-1-enoyl-CoA (6-oxo-1-enoyl-CoA), a common intermediate of the BzCoA degradation pathway. (ii) 6-Oxo-1-enoyl-CoA hydrolase/hydratase catalyzed the defluorination of 2-F-6-OH-1-enoyl-CoA to 2-oxo-6-OH-1-enoyl-CoA and HF again via water addition to an F-enoyl-CoA functionality. Based on these in vitro results, we demonstrate a previously overseen capability of 2-F-benzoate degradation for many but not all tested facultatively and obligately anaerobic bacteria that degrade aromatic compounds via the BzCoA degradation pathway. In conclusion, the newly identified enzymatic defluorination by enoyl-CoA hydratases via alpha-fluorohydrin formation represents an abundant, physiologically relevant principle of enzymatic defluorination.